Complex Regional Pain Syndrome - GÜNDÜZ, OSMAN HAKAN (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2011)
Complex regional pain syndrome (CPRS) is a neuropathic pain disorder that can develop as a result of trauma, surgery or nerve injury, but many times no precipitating event is known. The pain is described as severe, constant, burning and/or deep aching. The hallmark of CRPS is pain and mobility problems disproportionate to the initial injury. Clinical features can include spontaneous limb pain, changes in skin color and temperature, swelling, vasomotor instability and autonomic dysfunction. The pathophysiology is not well understood, although progress is being made in better understanding the underlying mechanisms. The diagnosis of CRPS is generally clinical, but there are tests and procedures that may help support the diagnosis. The general awareness of CRPS is poor, and well-accepted treatment guidelines are lacking. Treatment should involve an interdisciplinary approach involving functional rehabilitation, pain management, and psychological treatment. Quality evidence supports the use of some medications. Other adjuvant therapies and more invasive treatments exist for refractory cases. Turk J Phys Med Rehab 2011;57:156-64.
Keywords: Complex regional pain syndrome; reflex sympathetic dystrophy; causalgia; shoulder hand syndrome; REFLEX SYMPATHETIC DYSTROPHY; SPINAL-CORD STIMULATION; SYNDROME TYPE-I; KETAMINE-INFUSION THERAPY; NEUROPATHIC PAIN; SYNDROME TYPE-1; INTRAVENOUS IMMUNOGLOBULIN; VASCULAR ABNORMALITIES; CEREBROSPINAL-FLUID; FOLLOW-UP